The Use of Relay Race Game to Increase The Students' Performance Speaking Ability - Nurhana; Ismail Latief (Institut Agama Islam Negeri Parepare, 2021)
Through observations made on students of SMPN 2 Pangale Kab, Mamuju Tengah, specially in class VIII it was found that students did not show motivation in learning English in school. Therefore, the researcher decided to use a Relay Race game to solve problems. Expected via a Relay Race Games are used, students motivation can be increased and improved see how the steps in the game can improve students motivation in learning English second year students of SMPN 2 Pangale Kab, Mamuju Tengah. The design of this study is a quantitative method using a quasi-experimental design (nonequivalent control group) with to groups, namely the exprtmental group and the control group. The study population was second year students in SMPN 2 Pangale Kab, Mamuju Tengah consisting of two classes in which the total number was 40 student. The sample of this research was purposive sampling technique. Researchers tookone class, VIII which was divided into two groups, the first group was VIII (A) as an experimental group consisting of 20 students and the second group was VIII (B) because the control group consisted of 20. Data collected trought pretes and posttest. The the method Relay Race game can improve students English ability the apply the discussion method. The results of this study indicate how students speak significantly improve.